Subcellular localization of tobramycin and vancomycin given alone and in combination in proximal tubular cells, determined by immunogold labeling. - Beauchamp, D (1992)
The subcellular localization of tobramycin and vancomycin in the renal cortices of rats was determined with ultrathin sections by immunogold labeling. Four groups of four rats each were treated for 10 days with saline (NaCl, 0.9%), tobramycin at dosages of 20 mg/kg of body weight per 12 h intraperitoneally, vancomycin at dosages of 25 mg/kg/12 h subcutaneously, or the combination tobramycin-vancomycin. On day 11, the animals were killed, and cubes of renal cortex were fixed overnight in phosphate-buffered glutaraldehyde (0.5%), dehydrated in ethanol, and embedded in Araldite 502 resin. Ultrathin sections were made and incubated with sheep antitobramycin antibody followed by protein A-gold (15-nm diameter) complex or rabbit antivancomycin antibody followed by gold (30-nm diameter)-labeled goat anti-rabbit antibody. For the double labeling, incubations were made on opposite sides of the grid. Tobramycin was detected over the lysosomes of proximal tubular cells, but the labeling was concentrated into small areas in the matrix of the lysosomes. Vancomycin was seen over the lysosomes of proximal tubular cells and was distributed uniformly throughout the matrix of the lysosomes. In rats treated with tobramycin-vancomycin, both drugs were still detected in lysosomes of proximal tubular cells. It is concluded that tobramycin and vancomycin accumulate in lysosomes of proximal tubular cells throughout 10 days of treatment and that vancomycin has no effect on the subcellular distribution of tobramycin.